INVESTIGATING THE FEASIBILITY OF CREATING A DISEASE REGISTRY IN EGYPT: A CASE STUDY OF DEMENTIA - Heikal, Shimaa Adel (AUC Knowledge Fountain, 2023)
The increased interest in evidence-based medicine led to the emergence of disease registries worldwide to help tackle the impact of chronic diseases by providing accurate data on several aspects of the disease care process. Age-associated diseases, particularly dementia, are growing worldwide with several implications and increased economic burden, especially in lower-income countries. In Egypt, there is a lack of accurate dementia prevalence and statistics data which hinders the establishment of appropriate disease management and care strategies. A national dementia registry would provide a massive valuable source of patient data that will significantly advance the disease management strategies and quality of patient care and impact health policy and decision-making. This study investigates the feasibility of creating a disease registry for dementia in Egypt by interviewing 24 relevant national and international experts to evaluate their perceptions, knowledge, and opinions, then provide recommendations for the most appropriate registry model to be developed in Egypt. Several core themes emerged from the analysis of experts’ interviews discussing many points that should direct the creation of any registry in Egypt. Learning from other successful registries, comparing their experiences, and applying them to Egyptian culture imposes an excellent opportunity for the registry establishment. The findings clearly provided the proposed best practices to be followed while initiating a national registry in Egypt in terms of functionality, planning, comprehension, governance, ethics, and challenges to avoid. The initiating process should start with a leading institution that brings together the potential stakeholders and defines the clear purpose and objectives of the registry to direct the planning and design. A research registry that focuses on collecting both clinical and demographic patients’ data, as well as diagnostic tests, is the most recommended in Egypt. A primary piloting phase should be the first step to test the functionality and effectiveness of the process then expansion of data and coverage can be a second step. To start collecting data for the first pilot, a few sites from the leading institution’s network can be included as the primary participants to ensure their involvement. A minimum data set is then developed to identify the data elements to be collected in the registry. The registry administrators should regularly monitor the data collected to ensure its integrity and develop a clear plan for providing access to users. Taken together, developing such a dataset is beneficial to the Egyptian healthcare system, which makes the investment worthwhile. Support and collaborative work from all stakeholders, along with suitable funding, are essential elements of the proper implementation of the project. Yet, it might seem to be an opportune time for initiating this kind of registry to address the needs and, at the same time, benefit from the strategic opportunities.